Comparative study of midazolam and fentanyl for the prevention of etomidate-induced myoclonus - Rasool, Sophiya; Gupta, Radha; Prakash, Sukriti (Asian Journal of Medical Sciences, 2023)
Background: Etomidate is one of the popular rapidly acting inducing agents with cardio-stable profile but associated with side effects such as myoclonus. Myoclonus can lead to regurgitation, prolapse of vitreous in open globe or many other complications. Aims and Objectives: The objectives are as follows: To compare the efficacy of Fentanyl and midazolam for prevention of Etomidate induced myoclonus. To study the hemodynamic parameters and side effects of midazolam and fentanyl in patients with myoclonus after etomidate injection. Materials and Methods: Eighty patients scheduled for elective surgeries under general anesthesia were randomly allotted into two groups of 40 patients each. Group F – fentanyl 1 μg/kg and Group M – midazolam 0.03 mg/kg were administered as pre-treatment before induction by Etomidate. After injection of Etomidate, incidence of myoclonus was observed along with the change in hemodynamic parameters (heart rate [HR], systolic blood pressure [SBP], diastolic blood pressure [DBP], and mean arterial pressure [MAP]). Comparison of hemodynamic parameters between 2 groups was done at pre-treatment, 1 min and 2 min after induction and 1 min after intubation. Results: Both fentanyl and midazolam reduced the incidence of myoclonus. However, fentanyl was more effective in decreasing incidence as well severity of myoclonus. Fentanyl was associated with more stable hemodynamic parameters such as HR, SBP, DBP, and MAP 1 min after intubation (P<0.05). In both the groups, there was no increased incidence of PONV. Conclusion: Fentanyl 1 μg/kg or midazolam 0.03 mg/kg can reduce etomidate induced myoclonus. However, fentanyl was more effective in decreasing incidence as well severity of myoclonus and was associated with stable hemodynamic parameters as compared to midazolam.